1997
DOI: 10.1046/j.1365-2796.1997.91105000.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of primary Raynaud's syndrome with traditional Chinese acupuncture

Abstract: Abstract. Appiah R, Hiller S,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 17 publications
0
27
1
2
Order By: Relevance
“…A possible explanation is that cold weather is always a contributing factor in initiating the attacks but that, once they have started, the overall decreased sympathetic tone in the blood vessels, nerves and surrounding connective tissue due to consistent myofascial work may reduce their duration and severity. This is in contrast to previous studies using interventions such as acupuncture, which demonstrated a marked decrease in the frequency but not in the duration or severity of each episode (Appiah, 1997). In comparison, studies using the fish-oil supplements found that the onset of PRP episodes following exposure to cold could be delayed through ingestion of omega-3 fatty acids (DiGiacomo et al, 1989).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…A possible explanation is that cold weather is always a contributing factor in initiating the attacks but that, once they have started, the overall decreased sympathetic tone in the blood vessels, nerves and surrounding connective tissue due to consistent myofascial work may reduce their duration and severity. This is in contrast to previous studies using interventions such as acupuncture, which demonstrated a marked decrease in the frequency but not in the duration or severity of each episode (Appiah, 1997). In comparison, studies using the fish-oil supplements found that the onset of PRP episodes following exposure to cold could be delayed through ingestion of omega-3 fatty acids (DiGiacomo et al, 1989).…”
Section: Discussioncontrasting
confidence: 86%
“…One study noted some success in reducing frequency and severity of Raynaud attacks through the use of low level laser therapy (Hirschl et al, 2004). Another examined the use of Chinese acupuncture in the treatment of PRP and it was observed that a reduction in frequency of vasospastic attacks lasted for 10 months following treatments, comparable to the effectiveness of calcium-channel blockers (Appiah, 1997). However, due to the complexity of PRP and the lack of an adequate level of proof with any one of these alternative treatments, it is agreed that the best approach thus far is avoidance of the precipitating factors and conservative lifestyle changes (Block and Sequeira, 2001).…”
Section: Alternative Treatmentsmentioning
confidence: 99%
“…Biofeedback was also not eff ective. In contrast, two studies investigating the eff ects of acupuncture revealed signifi cant benefi ts [11,12]. In three studies, low level laser therapy reduced the frequency and severity of RP attacks.…”
Section: Non-pharmacologic Approachmentioning
confidence: 98%
“…Although there has been a lack of adequate study data from RP patients with obstructive vascular disease involving the digital arteries, antithrombotic therapy with low-dose aspirin 75 -100 mg daily has been recommended for all patients with concomitant peripheral arterial occlusive disease [ESM 2,12]. In patients who develop critical digital ischaemia despite vasodilator therapy that is believed to be due to new onset of arterial occlusion, therapeutic-dose anticoagulation with either low-molecular-weight heparin (LMWH) or UFH might be considered to reduce the extent of ischaemic injury by preventing clot …”
Section: Antiplatelet and Anticoagulant Therapymentioning
confidence: 99%
“…42 Behavioral modification with biofeedback has helped many patients, and acupuncture has even proved beneficial in one small study. 43,44 We empirically treat patients with digital ulcers with pentoxifylline until their ulcers have resolved. The digital ulcers are treated with local care and judicious use of antibiotics for cellulitis.…”
Section: Treatment and Outcomementioning
confidence: 99%